An insight into the isolation, enumeration, and molecular detection of Listeria monocytogenes in food - Law, Jodi Woan-Fei; Ab Mutalib, Nurul-Syakima; Chan, Kok-Gan; Lee, Learn-Han (Frontiers in Microbiology, 2015)
Listeria monocytogenes, a foodborne pathogen that can cause listeriosis through the consumption of food contaminated with this pathogen. The ability of L. monocytogenes to survive in extreme conditions and cause food contaminations have become a major concern. Hence, routine microbiological food testing is necessary to prevent food contamination and outbreaks of foodborne illness. This review provides insight into the methods for cultural detection, enumeration and molecular identification of L. monocytogenes in various food samples. There are a number of enrichment and plating media that can be used for the isolation of L. monocytogenes from food samples. Enrichment media such as buffered Listeria Enrichment Broth (BLEB), Fraser broth and University of Vermont Medium (UVM) Listeria enrichment broth are recommended by regulatory agencies such as FDA-BAM, USDA-FSIS and ISO. Many plating media are available for the isolation of L. monocytogenes, for instance, PALCAM, Oxford and other chromogenic media. Besides, reference methods like FDA-BAM, ISO 11290 method and USDA-FSIS method are usually applied for the cultural detection or enumeration of L. monocytogenes. MPN technique is applied for the enumeration of L. monocytogenes in the case of low level contamination. Molecular methods including polymerase chain reaction (PCR), multiplex polymerase chain reaction (mPCR), real-time/quantitative polymerase chain reaction (qPCR), nucleic acid sequence-based amplification (NASBA), loop-mediated isothermal amplification (LAMP), DNA microarray and Next Generation Sequencing (NGS) technology for the detection and identification of L. monocytogenes are discussed in this review. Overall, molecular methods are rapid, sensitive, specific, time- and labour-saving. In future, there are chances for the development of new techniques for the detection and identification of foodborne with improved features.